2014
DOI: 10.1007/s10067-014-2776-y
|View full text |Cite
|
Sign up to set email alerts
|

The Social Gap Index and the prevalence of osteoarthritis in the community: a cross-sectional multilevel study in Mexico

Abstract: Multilevel studies have gained importance for highlighting social inequalities in health. These associations have been reported previously in diseases such as arthritis and chronic pain. We conducted a cross-sectional study using multilevel analysis to identify individual and contextual factors associated with the variation of prevalence of osteoarthritis (OA) in the Mexican population. The sample included 17,566 individuals of which 10,666 (60.7%) were women. The relationship between individual and contextual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Data from the Health, Well-Being, and Aging in Latin America and the Caribbean Study (SABE) studies, showed that 23.8% to 55.6% of adults aged 60 years and above had self-reported arthritis and was significantly associated with limitation in activities of daily living (ADL) in all studied populations [3]. Data from The Community Oriented Program for the Control of Rheumatic Diseases (COPCORD) questionnaire showed a 9.5% prevalence of osteoarthritis in Mexico, the primary form of arthritis to affect middle and older adults, increasing to 21.4% in those 65 years and over [4]. Based on the 2010-2012 National Health Interview Survey in the U.S., by 2040 the prevalence of arthritis in adults is expected to increase to 25.9%, and the number of adults with activity limitation due to arthritis will increase to 11.4% [5].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Health, Well-Being, and Aging in Latin America and the Caribbean Study (SABE) studies, showed that 23.8% to 55.6% of adults aged 60 years and above had self-reported arthritis and was significantly associated with limitation in activities of daily living (ADL) in all studied populations [3]. Data from The Community Oriented Program for the Control of Rheumatic Diseases (COPCORD) questionnaire showed a 9.5% prevalence of osteoarthritis in Mexico, the primary form of arthritis to affect middle and older adults, increasing to 21.4% in those 65 years and over [4]. Based on the 2010-2012 National Health Interview Survey in the U.S., by 2040 the prevalence of arthritis in adults is expected to increase to 25.9%, and the number of adults with activity limitation due to arthritis will increase to 11.4% [5].…”
Section: Introductionmentioning
confidence: 99%
“…From a “social determinants of health” perspective, it seems that the conditions of social disadvantage faced by this rural community result in health inequities that condition the manifestation of arthritis. This social disparity has also been observed in a large Mexican multilevel epidemiological study where the prevalence of OA was clearly associated with higher social underdevelopment [ 42 ] and in a large Latin American study where the rheumatoid arthritis disabling effects were higher in people of low socioeconomic status [ 43 ].…”
Section: Discussionmentioning
confidence: 54%
“…Usually, back pain occurs at night, disrupting sleep. Aside from the fact that chronic diseases affect people during their productive years, limiting their earning potential, as treatments tend to be expensive, they further exacerbate the financial situation of those affected and their primary caretakers (Mould-Quevedo et al, 2008; Rodríguez-Amado et al, 2016).…”
Section: Impact Of Ankylosing Spondylitismentioning
confidence: 99%